2022
DOI: 10.1093/hr/uhac232
|View full text |Cite
|
Sign up to set email alerts
|

Genic male and female sterility in vegetable crops

Abstract: Vegetable crops are greatly appreciated for their nutritional and health beneficial components. Hybrid seeds are widely used in vegetable crops for advantages such as high yield and improved resistance, which require the participation of male (stamen) and female (pistil) reproductive organs. Male- or female-sterile plants are commonly used for production of hybrid seeds or seedless fruits in vegetables. In this review, we will focus on the types of genic male sterility and factors affecting female fertility, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 158 publications
0
7
0
Order By: Relevance
“…Male sterility, which encompasses anther morphological defects, microsporogenesis issues, impaired pollen development, and disrupted pollen function, may also be a contributing factor [ 49 ]. Similarly, female sterility can arise from defects in the ovaries and ovules [ 50 , 51 ]. A previous study exploring the morphology of L. indica identified anther dehiscence and abnormal embryonic sac development as the primary causes of L. indica sterility.…”
Section: Discussionmentioning
confidence: 99%
“…Male sterility, which encompasses anther morphological defects, microsporogenesis issues, impaired pollen development, and disrupted pollen function, may also be a contributing factor [ 49 ]. Similarly, female sterility can arise from defects in the ovaries and ovules [ 50 , 51 ]. A previous study exploring the morphology of L. indica identified anther dehiscence and abnormal embryonic sac development as the primary causes of L. indica sterility.…”
Section: Discussionmentioning
confidence: 99%
“…Cross-pollinating nature and huge inbreeding depression harden inbred lines development in onion, whereas, development of CMS lines through genome editing or RNAi mediated could be possible. Previous, research demonstrated that male sterility was triggered by downregulating some potential genes in various crops, including SAMDC (Cheng et al, 2022), CsSUT1I (Sun et al, 2019), MSH1 (Zhao et al, 2016, AcMSH1 , and CsHT1 (Cheng et al, 2015). In order to develop male sterile lines in Alliums, this gene would either be knocked down or eliminated in onions.…”
Section: Development Of Cms Linementioning
confidence: 99%
“…However, the traditional method of producing tomato hybrid seeds involves labor-intensive processes, such as manual emasculation and hand pollination, leading to increased costs and the risk of self-pollination impurities [ 3 , 4 ]. To address these challenges, researchers have explored the suitability of male sterile plants as female progenitors in the production of tomato hybrid seeds [ 4 , 5 ]. Different genes controlling male sterility have been examined, and their applications in plant breeding have been evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Since the first report of a male sterile mutant in tomatoes in 1915, over 55 male sterile alleles have been identified and categorized into three types: sporogenous, functional, and structural sterility [ 5 , 6 ]. Most tomato male sterile mutants are of the sporogenous type [ 7 ], with only a few having been cloned, such as SlMS10 and SlMS32 .Both of these encode a basic helix–loop–helix (bHLH) transcription factor [ 8 , 9 , 10 ] and are homologous to DYT1 and bHLH10/89/90 in Arabidopsis , respectively [ 8 , 10 ].…”
Section: Introductionmentioning
confidence: 99%